2011
DOI: 10.1111/j.1752-0606.2011.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Homework Use, Experience of Barriers to Homework, and Attitudes About the Barriers to Homework Among Couples and Family Therapists

Abstract: Homework is a therapeutic process that has strong theoretical and empirical basis, but existing research has focused on "compliance" rather than considering the broader and more clinically meaningful construct of "engagement." Absent in the literature is empirical study of the barriers to engagement or study of homework use among couple and family therapists (CFTs). The current study investigates the frequency and type of homework, as well as the influence of homework compliance, quality of compliance, and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…A lottery incentive was provided, with one in every 25 respondents randomly selected to receive a $25 Amazon gift card, for a total of seven incentives. The final response rate was 34.8% ( N = 174), a rate consistent with previous studies of family therapists (Dattilio, Kazantzis, Shinkfield, & Carr, ). Our university's institutional review board approved this study.…”
Section: Methodssupporting
confidence: 86%
“…A lottery incentive was provided, with one in every 25 respondents randomly selected to receive a $25 Amazon gift card, for a total of seven incentives. The final response rate was 34.8% ( N = 174), a rate consistent with previous studies of family therapists (Dattilio, Kazantzis, Shinkfield, & Carr, ). Our university's institutional review board approved this study.…”
Section: Methodssupporting
confidence: 86%
“…We then sorted the names by number in ascending order and selected the first 500 candidates for recruitment. Consistent with earlier studies of family therapists (Dattilio, Kazantzis, Shinkfield, & Carr, 2011), our response rate was 34.8% (N = 174). The sample consisted of family therapists from 38 states, most of whom identified as women (n = 126, 72.4%) and as white (n = 151, 86.8%).…”
Section: Sample and Recruitmentsupporting
confidence: 89%
“…This exploratory study sought to understand how family therapists engage in political and policy advocacy. Although a 34.8% response rate has been suggested as acceptable for mailed surveys (Dattilio et al., ), our findings can only be generalized with restraint. The political interests of this self‐selected sample might not be representative of family therapists in general.…”
Section: Discussionmentioning
confidence: 53%
“…First, the fact that someone is trying something related to therapy on many days can be seen as a positive, given the busy life and current stress levels of clients. Second, this could be an artifact of the therapy, and while many therapists prescribe homework (Dattilio et al., ), therapists in this study could have asked that clients do something on 1 or 2 days between sessions. It is also important to realize that this study was on the early stages of therapy and it is possible that clients will try more things from therapy at different therapy stages.…”
Section: Discussionmentioning
confidence: 99%
“…Most therapy is designed to have an influence on couples between sessions with homework or out of treatment activities being a large part of couple therapy (Dattilio, 2002). Dattilio, Kazantzis, Shinkfield, and Carr (2011) found that close to 97% of therapists use homework in couple therapy. Research also shows that clients do things on their own to help improve their relationship (Johnson, Nelson, & Allgood, 1998).…”
Section: Trying Something From Therapymentioning
confidence: 99%